A living man from Africa : Jan Tzatzoe, Xhosa chief and missionary, and the making of nineteenth-century South Africa - Levine, Roger S. (New directions in narrative history., 2011)
Born into a Xhosa royal family around 1792 in South Africa, Jan Tzatzoe was destined to live in an era of profound change - one that witnessed the arrival and entrenchment of European colonialism. This title reclaims Tzatzoe's lost story and analyzes his contributions to, and experiences with, the turbulent colonial world.